Peran Pemerintah dan Masyarakat Dalam Pembangunan Desa Titiwangi Kecamatan Candipuro Kabupaten Lampung Selatan - Julistia, Ira; Kurniati, Erlin (CV ODIS, 2024)
This research aims to describe the role of community government in the development of Titiwangi Village, Candipuro District, South Lampung Regency, and the supporting and inhibiting factors. This study used a descriptive qualitative method. The informants in this research ranged from the Village Head (as a key informant), Village Officials, Hamlet Heads, BPD, and Karang Taruna, to the general public. The data collection technique was carried out using triangulation (combination), data analysis was inductive, and qualitative research results emphasized meaning rather than generalization. The research results show that the role of the government community in the development of Titiwangi Village is quite good and balanced. The collaboration that occurs is mutualistic in nature where the parties involved understand each other's position and role in village development. The village government plays a role in facilitating the community and providing good direction to the community regarding the development goals that will be implemented. The community plays a role in contributing thoughts, energy, and property for the success of development. Meanwhile, the supporting factor for government-community cooperation is the humane approach taken by the village government towards society, and the community itself has a good understanding of its position and role in development. Apart from that, the inhibiting factors are the lack of public awareness of environmental cleanliness and the government's continued assumption that the community is subordinate and the object of development supervision